The physical environment and major plant communities of the Tankwa- Karoo National Park - Francine Rubin (Koedoe: African Protected Area Conservation and Science, 1998)
Apart from Acocks (1988) there are no published descriptions of the vegetation of the greater Tanqua and Doring River drainage basin (Bayer et al. 1993). A botanical and physical description of the Tankwa- Karoo National Park (TKRNP) which occurs in Veldtype 31b (Acocks 1988) is provided. The three dominant geological formations, older glacigenic deposits of the Dwyka Group, followed by the succession of siliciclas- tic sediments of the Permian Ecca Group, with flat dolerite sills and dykes, underlie eight distinct plant communities. The plant communities can be divided into large open plains dominated by Galenia africana and Tripteris sp. in the erosion rills, Malephora luteola and Augea capensis common in the low lying areas and Zygophyllum microcarpum, Brownanthus ciliatus and Galenia crystallina common on the more shaly concave plains and low shale hills. Slightly elevated rocky areas are dominated by Ruschia cf. robusta, Ruschia spinosa communities, while crusts of stemless mesembs such as Rhinephyllum macra denium, Hereroa fimbriata and Cheiridopsis acuminata are found on the desert paved areas. Annual Asteraceae covers all the denuded and sparsely vegetated areas after good winter rains while annual mesembs colonise on the more sodic sites. A total of 259 plant species were collected sporadically over a period of eight years, this includes 65 succulents and seven species endemic to the Tanqua Karoo and immediate adjacent area of the Roggeveld Mountain Range and Sutherland. Four Tanqua Karoo endemic species were found in the park.